2018
DOI: 10.1002/ps.4804
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in response to glyphosate treatment in fleabane (Conyza bonariensis) – glyphosate death response and candidate resistance genes

Abstract: We demonstrate that glyphosate resistance in C. bonariensis is not the result of EPSPS mutations or overexpression, but due to a non-target-site mechanism. A large number of genes are affected by glyphosate treatment. We present a list of candidate non-target-site-resistance (NTSR) genes in fleabane for future studies into these mechanisms. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 58 publications
5
28
0
Order By: Relevance
“…The mechanism of glyphosate resistance remains to be characterized fully in other NRR A. trifida biotypes as noted above, in several RR A. trifida accessions, 15,19,62 and in other species. 45,63 Future research objectives are to investigate cellular uptake and subcellular distribution of glyphosate 19,64 and transcriptome profiling 65 in Wisconsin A. trifida R and S phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of glyphosate resistance remains to be characterized fully in other NRR A. trifida biotypes as noted above, in several RR A. trifida accessions, 15,19,62 and in other species. 45,63 Future research objectives are to investigate cellular uptake and subcellular distribution of glyphosate 19,64 and transcriptome profiling 65 in Wisconsin A. trifida R and S phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of the present work show that until 192 and 288 HAT for GS and GR biotypes, respectively, the glyphosate treatment does not interfere negatively in RIN integrity (Figures 2, 3, 4, 5 and 6). Thus, for further molecular analysis such as RNA-Seq and RT-qPCR, the RNA integrity results indicate that studies can be performed in times higher than 24 and 48 HAT Hereward et al, 2018) to capture as much as possible the process of glyphosate plant detoxification ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been conducted in Conyza spp. with the objectives to understand the GR mechanisms (Feng et al, 2004;Ferreira et al, 2008;Peng et al, 2010;Ge et al, 2014;Cardinali et al, 2015;Tani et al, 2015;Moretti et al, 2017;Kleinman and Rubin, 2017;González-Torralva et al, 2017;Hereward et al, 2018;Amaro-Blanco et al, 2018). These studies have found that the GR mechanisms are related to herbicide transport, translocation, uptake, metabolism, and alterations at the 5-enolpyruvylshikimate 3-phosphate synthase (EPSPS) enzyme, which is the glyphosate target site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced dicamba translocation was found in dicamba‐resistant Kochia scoparia with no differences in dicamba metabolism, and a transcriptomics study suggested that increased flavonol pathway transcription was associated with dicamba resistance . Glyphosate resistance was investigated in Conyza bonariensis using transcriptomics, showing the lack of a resistance conferring mutation in the three EPSPS copies carried on each of three genomes of this hexaploid species, and producing a list of candidate genes that could be involved in non‐target‐site glyphosate resistance . The evolution of plant protoporphyrinogen oxidase genes is reviewed, along with implications for herbicide resistance .…”
mentioning
confidence: 99%